Komplikasi Okular pada Demam Dengue - Haikal Hamas Putra Iqra; Rabiul Priyantono; Mia Purnama (PT Kalbe Farma Tbk., 2024)
Ocular complications rarely occur in dengue fever, but were reported increasing. Several studies showed that cross-reactive antibody is responsible for ocular involvement in dengue. Blurred vision, followed by posterior segment involvement was seen in most cases. A simple examination in primary medical care such as the Amsler grid may detect scotoma and metamorphopsia. Early recognition of ocular involvement in dengue cases may prevent morbidity.